Photocatalytic performance of Fe-doped TiO2 nanoparticles under visible-light irradiation. (30th January 2017) - Ali, T; Tripathi, P; Azam, Ameer; Raza, Waseem; Ahmed, Arham S; Ahmed, Ateeq; Muneer, M
Abstract: The present work focuses on the synthesis, characterization and photocatalytic activity of a nanosized Fe-doped TiO2 photocatalyst. The samples were synthesized by the sol–gel method and characterized by using techniques such as x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive x-ray spectroscopy (EDS), UV–visible spectroscopy, photoluminescence (PL) spectroscopy, Raman spectroscopy and Fourier-transform infrared (FTIR). The powder XRD spectra revealed that the synthesized samples are pure and crystalline in nature and show a tetragonal anatase phase of TiO2 . The Raman spectroscopy also confirmed the formation of an anatase phase structure in both pure and Fe-doped TiO2 nanoparticles (NPs). The UV–visible and PL spectra illustrated the red shift in Fe-doped TiO2 NPs. The FTIR spectra indicated the vibrational band of the Ti–O lattice. The photocatalytic experimental results demonstrate that Fe-doped TiO2 NPs effectively degrade MB under visible-light illumination. Interestingly, the prepared TiO2 NPs with a dopant concentration of 3.0 mole% showed the maximum photocatalytic activity under investigation.